Pengabdian Masyarakat : Implementasi Teknologi Pendidikan di SMAN 4 Padang Sidempuan - Safrial Safrial (Lembaga Pengembangan Kinerja Dosen, 2025)
Technological advances have a significant impact on the world of education, including at the Senior High School (SMA) level. This community service aims to improve the understanding and application of educational technology at SMAN 4 Padang Sidempuan in order to improve the quality of learning. The methods used include teacher training, assistance in implementing technology in learning, and evaluation of the effectiveness of its application. The results show that the use of technology such as Learning Management System (LMS), interactive multimedia, and learning software increases student engagement and teaching effectiveness. The use of educational technology also contributes to improving the quality of learning that is more interactive and flexible. However, the challenges faced in implementing educational technology include the readiness of educators, school infrastructure, and the gap in access to technology for students. Therefore, a comprehensive approach is needed in developing human resources and utilizing more optimal technology.